A novel conformable embolic for selective transarterial embolization of acute hemorrhages: a technical note - Qian Yu; Osman Ahmed; Jiaqi Chen; Yousuf Islam; Brian Funaki; Mikin Patel (CVIR Endovascular)
Abstract Background Obsidio conformable embolic (OCE, Boston Scientific, MA) is a novel, radiopaque and conformable embolic. The purpose of this report is to describe its use for treatment of acute intra-abdominal hemorrhages. Methods and results Three patients presented with acute hemorrhage and were treated with OCE, including post-paracentesis hemorrhage, penetrating trauma to the liver, and blunt trauma in the spleen. All cases were performed under moderate sedation, with hemostasis achieved by end of procedure using less than 1 vial of OCE (0.2-0.4 ml). No severe adverse events occurred. None required repeated treatment. Short conclusion OCE is a safe and effective embolic agent for treatment of intra-abdominal or visceral hemorrhage. Future studies with larger sample sizes and longer follow-up are warranted.